Health information priorities for more effective implementation and monitoring of non-communicable disease programs in low- and middle-income countries: lessons from the Pacific. Issue 1 (December 2015) - Gouda, Hebe; Richards, Nicola; Beaglehole, Robert; Bonita, Ruth; Lopez, Alan
Abstract Background Non-communicable diseases (NCDs) place enormous burdens on individuals and health systems. While there has been significant global progress to guide the development of national NCD monitoring programs, many countries still struggle to adequately establish critical information systems to prioritise NCD control approaches. Discussion In this paper, we use the recent experience of the Pacific as a case study to highlight four key lessons about prioritising strategies for health information system development for monitoring NCDs: first, NCD interventions must be chosen strategically, taking into account local disease burden and capacities; second, NCD monitoring efforts must align with those interventions so as to be capable of evaluating progress; third, in order to ensure efficiency and sustainability, NCD monitoring strategies must be integrated into existing health information systems; finally, countries should monitor the implementation of key policies to control food and tobacco industries. Summary Prioritising NCD interventions to suit local needs is critical and should be accompanied by careful consideration of the most appropriate and feasible monitoring strategies to track and evaluate progress.